2019
DOI: 10.1088/1742-6596/1228/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Technology Foresight In The Virtual Learning Environment in Malaysia

Abstract: The government has adopted the Virtual Learning Environment (VLE) into the primary and secondary education system via the 1BestariNet project. Since this project is expected to consume more than RM 4 billion, it is vital to do technology foresight to identify the emerging technologies which can be integrated to the VLE system. Besides, the emerging technologies must also be ranked accordingly so that the government can be made aware from the most practical technologies to the least for future study or procurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As mentioned earlier, some scholars also use fuzzy methods to explore the performance evaluation of online learning and provide good suggestions for improvement. Those scholars include Çelikbilek et al [26], Lange [27], Ma et al [28], Shanmugam et al [29], and Wong et al [30]. In order to improve the data collection of fuzzy numbers, which is complicated and may reduce customers' willingness to answer questions, Chen et al [18] developed a discriminate index to determine whether a service item requires improvement by having customers rank how important a service item is to them and how satisfactory they found that service item to be.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, some scholars also use fuzzy methods to explore the performance evaluation of online learning and provide good suggestions for improvement. Those scholars include Çelikbilek et al [26], Lange [27], Ma et al [28], Shanmugam et al [29], and Wong et al [30]. In order to improve the data collection of fuzzy numbers, which is complicated and may reduce customers' willingness to answer questions, Chen et al [18] developed a discriminate index to determine whether a service item requires improvement by having customers rank how important a service item is to them and how satisfactory they found that service item to be.…”
Section: Introductionmentioning
confidence: 99%
“…12,[29][30][31][32][33][34] The name of the technique originates from Greek mythology, where in the oracle of Delphi, which was dedicated to the God Apollo, the ancient Greeks questioned the gods. 12,[29][30][31][32][33][34] The name of the technique originates from Greek mythology, where in the oracle of Delphi, which was dedicated to the God Apollo, the ancient Greeks questioned the gods.…”
Section: Delphi Techniquementioning
confidence: 99%
“…The Delphi technique was developed by the RAND Corporation in the 1950s by Olaf Helmer, Norman Dalkey, Ted Gordon, and associates under funding from the United States Air Force as a technique to apply expert input systematically using a series of questionnaires with results feedback after every round. 12,[29][30][31][32][33][34] The name of the technique originates from Greek mythology, where in the oracle of Delphi, which was dedicated to the God Apollo, the ancient Greeks questioned the gods. In the oracle, it was possible to obtain answers and prophecies made by the priestesses of Apollo in trance state.…”
Section: Delphi Techniquementioning
confidence: 99%
See 2 more Smart Citations